Labral Morphologic Characteristics in Patients With Symptomatic Acetabular Dysplasia. (September 2015) - Sankar, Wudbhav N.; Beaulé, Paul E.; Clohisy, John C.; Kim, Young-jo; Millis, Michael B.; Peters, Christopher L.; Podeszwa, David A.; Schoenecker, Perry L.; Sierra, Rafael J.; Sink, Ernest L.; Sucato, Daniel J.; Zaltz, Ira
Background: The morphologic characteristics of the labrum in patients with symptomatic acetabular dysplasia have been described to some extent in smaller retrospective series, but the need remains to further define these disease characteristics and their importance as a diagnostic feature of hip instability. Purpose: To (1) characterize the morphologic characteristics of the labrum in patients with symptomatic acetabular dysplasia and (2) test the relationships between specific labral variants, severity of dysplasia, and duration of symptoms. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Thirteen surgeons from 10 centers enrolled patients undergoing periacetabular osteotomy (PAO) for symptomatic acetabular dysplasia from 2008 to 2014. Patient demographics, presenting characteristics, preoperative radiographic data, operative data, and intraoperative findings were prospectively collected and retrospectively reviewed. Results: A total of 942 patients (972 hips) met the initial inclusion criteria, with a mean age of 25.2 years (range, 9-51 years; 84% female, 16% male). In addition to having PAO, 52.6% of hips had an anterior arthrotomy and 19.8% had a hip arthroscopy either to perform an osteochondroplasty of the femoral head-neck junction or to address labral pathologic changes. Of these 553 hips in which the labrum was visualized, labral morphologic status was graded as hypertrophic in 50%, normal in 45%, hypoplastic in 4%, and ossified in less than 1%. Decreased lateral center-edge angle and anterior center-edge angle and increased acetabular inclination were associated with labral hypertrophy, but chronicity of symptoms was not. Of the 553 hips, 64% had tears of the labrum, with the majority being degenerative-type tears. Conclusion: Labral pathologic changes are common in patients with symptomatic acetabular dysplasia. Labral hypertrophy, however, is not a universal finding, particularly in hips with mild dysplasia, and therefore should not be considered a reliable diagnostic criterion for instability.